2016
DOI: 10.4236/sar.2016.42002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Heart Ischemia in Blood Serum

Abstract: Our aim was to study the selected cases of the patients with ischemic heart disease and to analyze the structure of blood serum of patients in comparison with control serum of healthy subjects by methods: synchronous fluorescence fingerprint and atomic force microscopy that are still not used in clinical practice. Our results of fluorescence analysis showed that blood serum of all patients with ischemic heart disease decreased intensity of fluorescence in comparison with control blood serum. Endogenous fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…During diseases but also other physiological disturbances of homeostasis, the composition of body fluids (saliva) is changed. These results are reflected in differences on SFS and it is V. Tomečková et al DOI: 10.4236/sar.2017.54004 40 Spectral Analysis Reviewslikely to identify pathological process[17].…”
mentioning
confidence: 99%
“…During diseases but also other physiological disturbances of homeostasis, the composition of body fluids (saliva) is changed. These results are reflected in differences on SFS and it is V. Tomečková et al DOI: 10.4236/sar.2017.54004 40 Spectral Analysis Reviewslikely to identify pathological process[17].…”
mentioning
confidence: 99%
“…The increase in porphyrin derivatives indicative of subversion of heme metabolism was consistent with increase in the serum iron at 72 h BDL and can be used as potential intrinsic biomarkers of molecular and cellular changes in cholestasis for early diagnosis (Croce et al, 2011). There is also evidence that SFS can be used to diagnose heart ischemia (Tomečková et al, 2016) and various bowel diseases (Tomečková et al, 2018), but the relevant fluorophores in each of these studies were not identified. It is important to note that autofluorescence measurements cannot be explored as diagnostic tools simply based on their simplicity and label free approach.…”
Section: Applications Of Blood Autofluorescencementioning
confidence: 99%
“…These methods include uorescence spectroscopy (FS) which has been validated as a diagnostic tool during various pathologies, e.g. diastolic dysfunction, 16 non-small-cell lung carcinoma, 17 ischemic heart disease, 18 diabetes mellitus 19 and many others. The method is based on the analysis of the autouorescent substances occurring in the sample (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that it is mostly used for in vitro studies, such as for differentiating between normal and cancerous cells [24][25][26] or detection of viruses, 27 it is also used for novel studies and diagnostics. Examples of such studies include the detection of signicant differences between the blood serum of patients and healthy controls, which were observed during ischemic heart disease 18 and breast cancer 28 , together with assessment of changes in the dermis. 29 In our pilot study we assessed the diagnostic potential of FS, IRS and AFM for diabetes mellitus using tear uid.…”
Section: Introductionmentioning
confidence: 99%